1991
DOI: 10.1021/ma00011a068
|View full text |Cite
|
Sign up to set email alerts
|

Chemoenzymatic synthesis of novel sucrose-containing polymers

Abstract: Communications to the Editor Chemoenzymatic Synthesis of Novel Sucrose-Containing Polymers Typical chemical catalysts provide the chemoselectivity required for the preparation of high molecular weight poly(esters, amides, ols, acrylates, etc.) while enhancing reaction rates. There is an increasing need, however, to impart additional selectivity (e.g., regio-or stereoselectivity) in the synthesis of polymers.1 This is particularly important in the synthesis of optically active polymers or the synthesis of linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
54
0
4

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(59 citation statements)
references
References 2 publications
1
54
0
4
Order By: Relevance
“…In addition to the obvious advantage of enhancing the solubilities of organic substrates, organic solvents can lead to unusual chemistry when enzyme-catalyzed reactions that are infeasible in an aqueous medium become favored in a nonaqueous one (7). In organic solvents, serine proteases are promising catalysts for organic synthesis and the preparation of unusual polymers (8)(9)(10)(11). A triple variant of subtilisin E with enhanced activity in dimethylformamide (DMF) was described in an earlier report (12).…”
mentioning
confidence: 99%
“…In addition to the obvious advantage of enhancing the solubilities of organic substrates, organic solvents can lead to unusual chemistry when enzyme-catalyzed reactions that are infeasible in an aqueous medium become favored in a nonaqueous one (7). In organic solvents, serine proteases are promising catalysts for organic synthesis and the preparation of unusual polymers (8)(9)(10)(11). A triple variant of subtilisin E with enhanced activity in dimethylformamide (DMF) was described in an earlier report (12).…”
mentioning
confidence: 99%
“…high temperature or strict exclusion of moisture) [5,6,16]and the metal catalysts may be problematic for certain product end uses especially for medical use. [7] Lipase can catalyze esterification reactions at mild temperatures [8][9][10].These characteristics motivated theirs study as catalysts for polyesterifications.Recently,enzymatic designing and synthesizing of environmentally acceptable polymeric materials has become an effective method. Unless chemical catalysis lipase catalyzed condensation polymerizations are metal-free and enzymes are derived from natural resources.…”
Section: Introductionmentioning
confidence: 99%
“…For this, the development of short and easy routes for the preparation of larger quantities of these target molecules was necessary. A high degree of regioselectivity can be achieved by the enzymatic approach (Patil et al, 1991;Potier et al, 2000), although some disadvantages and limitations can be found in the use of enzymes (low stability of the enzymes in organic solvents or the correct choice of reagents for introducing the unsaturation, (Chen and Park, 2000). The functionalization of carbohydrates normally involves various protection-deprotection steps, which take a lot of experimental time (Jarosz and Mach, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Sucrose-containing polymers, having a polyvinyl backbone and pendant sucrose moieties, have been obtained by polymerization or copolymerization of sucrose derivatives -esters, ethers, and acetals, bearing a carbon-carbon double bond (Fig. 5), (Fanton et al, 1992;Ferreira et al, 2000;Jhurry et al, 1992;Patil et al, 1991). The monomers have been prepared either by multistep synthesis, leading to defined compounds and subsequently a well-defined polymerization processes (Fig.…”
mentioning
confidence: 99%